1991
DOI: 10.1210/endo-128-2-741
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine and 3,3′,5-Triiodothyronine Are Glucuronidated in Rat Liver by Different Uridine Diphosphate-Glucuronyltransferases*

Abstract: Male Wistar rats were treated with 50 mg 3,3',4,4'-tetrachlorobiphenyl (TCB)/kg BW or vehicle. After 4 days, the livers were isolated and perfused for 90 min with 2 nM [125I]T3 or 10 nM [125I]T4 in Krebs-Ringer medium containing 1% albumin. Deiodination and conjugation products and remaining substrates were determined in bile and medium samples by Sephadex LH-20 chromatography and HPLC. TCB treatment did not affect hepatic uptake and metabolism of T3. However, biliary excretion of T4 glucuronide was strongly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 22 publications
4
76
1
1
Order By: Relevance
“…McCleary (2001) began development of this assay by modifying/combining the methods of Beetstra et al (1991), and Barter and Klaassen (1992a), which describe an assay previously validated for use on rodents. I further modified McCleary's methods for use in quail.…”
Section: Development Of An Assay For Measuring Avian Udp-gt Activity mentioning
confidence: 99%
“…McCleary (2001) began development of this assay by modifying/combining the methods of Beetstra et al (1991), and Barter and Klaassen (1992a), which describe an assay previously validated for use on rodents. I further modified McCleary's methods for use in quail.…”
Section: Development Of An Assay For Measuring Avian Udp-gt Activity mentioning
confidence: 99%
“…Cheek et al (35) found that it was only the hydroxylated PCBs, not the parent compounds, that bound to transthyretin and thyroid-binding globulin and report that they had the same affinity for transthyretin as thyroid hormone. They may also activate uridine diphosphate-glucuronyltransferase, which then increases the biliary excretion of T 4 -glucuronide (31,36). In a recent review, Brucker-Davis (37) concluded that except in the fetus the major mode of action of coplanar congeners is through increased glucuronidation, whereas the ortho-substituted congeners, and particularly their oxidative metabolites, act through multiple other pathways, including interference with transport proteins, direct action on the thyroid gland, and changes in the kinetics of thyroid hormone metabolism.…”
Section: Thyroid Diseasementioning
confidence: 99%
“…Analysis of thyroxin UDP-glucuronosyltransferase (T 4 UDPGT): T 4 UDPGT activities in hepatic microsomes were determined according to the method of Beetstra et al [2]. The microsome sample (1 mg protein/ml) was incubated with 1 µM T 4 (Sigma, St. Louis, MO, U.S.A.) and 0.1 µCi 125 I-T 4 (New England Nuclear, Boston, MA, U.S.A.) in 0.1 M Tris-HCl buffer (pH 7.4) containing 5 mM MgCl 2 and 0.05% Brij 56 (Sigma, St. Louis, MO, U.S.A.).…”
Section: Animals and Treatmentmentioning
confidence: 99%